2007
DOI: 10.1111/j.1471-6712.2007.00466.x
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of surviving spouse of terminally ill spouse: a phenomenological study of an altruistic perspective

Abstract: The aim of the study was to illuminate the experiences of surviving relatives in connection with their care at home of terminally ill, dying spouses, followed by an outline of the need for palliative assistance by the district nurse. Qualitative interviews with eight surviving relatives have been analysed on the basis of the phenomenological method. The essence of these phenomena was the loving promise to the terminally ill and dying spouse in which the shared grief, structural disintegration and powerlessness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…The findings revealed complex negotiations between family and patients about moving into a nursing home (often dictated by need rather than preference); the use of the patient’s personal historical identity and previous wishes to guide decision-making in the absence of overt preferences; and difficulties for the family in balancing the patient and their own wishes. Studies conducted in Canada, Japan and Denmark, mainly about cancer patients, showed that in some situations a preference for home was dyadic and equally important to patients and caregivers [48,49]; the result of a ‘mutual pact’ or promise to the patient, sometimes made in the context of a hospital admission or involving reciprocate care [50,51]. Some caregivers expressed a sense of achievement when the patient died at home, whilst others felt lack of choice, guilt and sorrow, depending on the outcome [50,51].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings revealed complex negotiations between family and patients about moving into a nursing home (often dictated by need rather than preference); the use of the patient’s personal historical identity and previous wishes to guide decision-making in the absence of overt preferences; and difficulties for the family in balancing the patient and their own wishes. Studies conducted in Canada, Japan and Denmark, mainly about cancer patients, showed that in some situations a preference for home was dyadic and equally important to patients and caregivers [48,49]; the result of a ‘mutual pact’ or promise to the patient, sometimes made in the context of a hospital admission or involving reciprocate care [50,51]. Some caregivers expressed a sense of achievement when the patient died at home, whilst others felt lack of choice, guilt and sorrow, depending on the outcome [50,51].…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted in Canada, Japan and Denmark, mainly about cancer patients, showed that in some situations a preference for home was dyadic and equally important to patients and caregivers [48,49]; the result of a ‘mutual pact’ or promise to the patient, sometimes made in the context of a hospital admission or involving reciprocate care [50,51]. Some caregivers expressed a sense of achievement when the patient died at home, whilst others felt lack of choice, guilt and sorrow, depending on the outcome [50,51]. In Morecambe Bay (UK), Thomas et al studied the preferences of 41 patients with advanced cancer and found they were strongly influenced by an assessment of caregivers’ capacity to care, irrespective of caregivers’ expressed desire to do it [52].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over time, some carers did identify with the term carer, yet others rejected it completely [26]. Some caregivers preferred to be self-sufficient, feeling that they did not yet need help [24], or that support from external paid carers was a potential intrusion [27,33]. Furthermore, acknowledging the caregiving role meant recognising that the ill person needed to be cared for [26].…”
Section: Resultsmentioning
confidence: 99%
“…Carers may be engulfed by the process and unable to access support because they do not have sufficient time, or are fearful of leaving the cared-for person [33,37]. Carers may also be concerned about diverting resources to themselves at the expense of the cared-for person [38].…”
Section: Resultsmentioning
confidence: 99%